"Aid in Dying" in the Courts. Issue 3 (May 2015) - Latham, Stephen R.
Abstract Three states—Oregon, Washington, and Vermont—have used straightforwardly democratic means to legalize the practice formerly known as "physician‐assisted suicide" but now termed "aid‐in‐dying." In two states—Montana and New Mexico—aid‐in‐dying has been declared legal neither by directly democratic action by citizens nor by representatively democratic action by the legislature but by court rulings in cases brought by aid‐in‐dying activists. The court case in New Mexico (Morris v. New Mexico, 2014) is undoubtedly of greater significance to the rest of the states. The Morris opinion is as interesting for what it declined to hold as for what it held.